Healing process of dogs' pulpless teeth after apicoectomy and root canal filling at different levels - Holland, R.; Otoboni Filho, José Arlindo [UNESP]; Bernabé, P. F.; Souza, V. de; Nery, Mauro Juvenal [UNESP] (Munksgaard Int Publ Ltd, 1993)
Dogs' teeth with infected root canals, were submitted to apicoectomy and the root canals were filled flush or 2 mm short. In a third group the canals were left unfilled and only the access openings were closed. One hundred and eighty days after the treatment, the animals were killed and the specimens prepared for histological analysis. Repair was not observed in the teeth with unfilled root canals. The healing observed in the teeth with root canals filled flush was less complete than the healing observed when the root canals were filled 2 mm short.
Keywords: Animal; Bacterial infection; Comparative study; Dog; Endodontics; Methodology; Pathology; Pathophysiology; Tooth development; Tooth disease; Tooth periapical disease; Tooth pulp; Wound healing; Animal; Apicoectomy; Bacterial Infections; Cementogenesis; Comparative Study; Dental Pulp Cavity; Dogs; Periapical Granuloma; Periapical Periodontitis; Root Canal Obturation; Root Resorption; Wound Healing